Volatility of Development Aid : From the Frying Pan into the Fire? - Hamann, A. (IMF Working Papers; Working Paper ;, 2006)
The positive impact of foreign aid is limited by the erratic behavior of aid flows. The introduction in 1999 of various initiatives anchored in Poverty Reduction Strategy Papers (PRSPs) which were aimed at strengthening coordination among donors, improving the design of financial support programs, and improving domestic records of policy implementation should have led to an improvement in the time series properties of aid flows. We find no evidence of any fundamental changes in the way aid has been delivered in the past five years. If anything, aid volatility has worsened somewhat and the information value of long-term lending commitments has declined. We take these results to mean that the main causes of the volatility and unpredictability of aid, and the broader issue of macroeconomic instability in low-income countries, have not been addressed in a systematic manner by the donor community.